Determinación de las dificultades que tienen los clientes en la elección de tiendas de autopartes en Lima Metropolitana en el Año 2020 - Muñiz Galdo, Hugo Bruno (2021)
The research raises the difficulty that customers have for choosing stores in the spare parts market, which may be motivated by different drivers which we want to know in the development of the study. Despite of the fact that the automotive sector in Peru has had a decade of sustained growth in new vehicles, it still has an old vehicle fleet, both require different kind of spare parts throughout their useful life to keep them in good condition and operability. Technology is a useful tool to solve many problems, so the study uses the hypothesis of a mobile application as a solution to the troubles for choosing spare parts stores in Metropolitan Lima. The literature review of functionality, mobile application development and m-commerce guide the study; to understand the needs of the sector's clients a field work is executed.